2002
DOI: 10.1021/cm0206542
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polymerized Multi-Layered Photonic Films

Abstract: A multilayer optical interference film has been developed using plasma-enhanced chemical vapor deposition (PECVD) of different organic precursor materials. A relatively large refractive index contrast for polymers (>0.2) is achieved by sequential plasma polymerization (PP) of octafluorocyclobutane (OFCB) and benzene. Gas-phase molecules of both precursors, excited by an argon plasma in a flowing afterglow reaction chamber, are deposited on a variety of substrates to form dense, pinhole-free, cross-linked polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 26 publications
2
55
0
Order By: Relevance
“…FTIR showed that the original OFCB ring structure was almost entirely destroyed during plasma polymerization, and that several different CF X structural groups were present in the film [15]. This agrees with the XPS results obtained from the PP-OFCB film reported above.…”
Section: Characterization Of the Filmssupporting
confidence: 91%
See 1 more Smart Citation
“…FTIR showed that the original OFCB ring structure was almost entirely destroyed during plasma polymerization, and that several different CF X structural groups were present in the film [15]. This agrees with the XPS results obtained from the PP-OFCB film reported above.…”
Section: Characterization Of the Filmssupporting
confidence: 91%
“…This indicates good control over the deposition conditions and also that PECVD of organic precursors can be utilized to deposit optical films with good thickness control. SEM studies of the cross-section of the 10-bilayer stack show that the individual layers are dense and have good adhesion [15].…”
Section: Fabrication Of a Notch Filtermentioning
confidence: 99%
“…This technique is a solventless (dry) process, resulting in organic films with high solvent, scratch, and corrosion resistance combined with excellent thermal and chemical stability. [152,153] The underlying mechanism of plasma polymerization involves in organic species undergoing fragmentation in plasma, resulting in excited sub-monomer species, free radicals, and ions that can react with each other in the plasma zone, or at the nascent surface layer (Fig. 10).…”
Section: Polymer Layersmentioning
confidence: 99%
“…[13][14][15][16][17] The most efficient vapor-responsive material, from a series of six polymers tested in this study, was plasma-polymerized methacrylonitrile (PP-MAN) (Fig. 1b and Supporting Information, SI).…”
mentioning
confidence: 99%